2021
DOI: 10.1002/alz.052095
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, mood and cognitive performance in older adults with cognitive impairment during the first wave of COVID 19 in Argentina

Abstract: Background In Argentina, government has established lock down on 19 March in order to decrease SARS‐COV 2 infection. These restrictions have remained effective for long time, with increase of anxiety depression and insomnia as shown in several studies. Older population was particularly at risk due to greater limitations to go out. Our objective was to evaluate the impact of confinement in quality of life, mood and cognitive performance of older adults with cognitive impairment. Method Longitudinal descriptive‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Regarding specific job types, several studies have reported psychological distress, burnout, sleep problems, and lower mood among physicians and other healthcare workers, particularly among those that experienced increased work-related stress and workload during the COVID-19 pandemic [28][29][30][31][32]. The formerly mentioned lockdown effects have also been demonstrated in specific patient cohorts, including patients with cognitive impairment [33].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding specific job types, several studies have reported psychological distress, burnout, sleep problems, and lower mood among physicians and other healthcare workers, particularly among those that experienced increased work-related stress and workload during the COVID-19 pandemic [28][29][30][31][32]. The formerly mentioned lockdown effects have also been demonstrated in specific patient cohorts, including patients with cognitive impairment [33].…”
Section: Discussionmentioning
confidence: 99%